INCREASING THE LEVEL OF PHYSICAL FITNESS OF SCHOOLCHILDREN THROUGH SPORTS ACTIVITIES (Scientific journal of the Fergana State University, 2024)
Today, the selection of young athletes is one of the pressing problems; it is important to increase the interest of students who are just starting to engage in athletics and to select the most talented.